Solid-phase synthesis of electroactive nanoparticles of molecularly imprinted polymers. A novel platform for indirect electrochemical sensing applications - Mazzotta, Elisabetta; Turco, Antonio; Chianella, Iva; Guerreiro, Antonio R.; Piletsky, Sergey A.; Malitesta, Cosimino (Elsevier, 2016)
Electroactive nanoparticles of molecularly imprinted polymers (MIP NPs) specific for a non-electroactive template (i.e., the antibiotic vancomycin) were for the first time synthesized by solid-phase synthesis adding two ferrocene-derivative monomers (namely, vinylferrocene and ferrocenylmethyl methacrylate) in different amount to polymerization mixture. MIP NPs were characterized by dynamic light scattering and by cyclic voltammetry studies. This latter allowed identifying the synthetic conditions determining the highest MIP NP electroactivity. The content of electrochemical label was verified by X-Ray Photoelectron Spectroscopy, which provided an estimation of the amount of ferrocene moieties in nanoparticle structure. In the attempt to apply MIP NPs for sensing applications, nanoparticles were anchored to a Nafion modified electrode by a simple self-assembly process and the indirect electrochemical detection of vancomycin was allowed by the change of ferrocene group redox properties upon the exposure to vancomycin. The observed behavior is believed to be due to hindering of the electron transfer process of the ferrocene redox sites within nanoparticles by their interaction with non-electroactive vancomycin. A novel sensing platform is thus developed by directly anchoring to the electrode surface an electroactive probe integrated within the imprinted polymer thus allowing the selective, easy and rapid electrochemical detection of non-electroactive target molecules.
Keywords: Molecularly imprinted polymers (MIPs); Electroactive MIP nanoparticles; Indirect electrochemical detection; Vancomycin